Finite Element Analysis Study of Titanium Hip Implant Using Abaqus Software - Asmawi, Rosli; Zurhana, Muhamad Abdul Naim (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Total hip arthroplasty, also known as the hip implant, is used to replace damaged bone on the hip joint. The stem design is crucial since it will influence the performance of hip arthroplasty. This study uses the finite element method to simulate the effect of different implant geometry to investigate the stress distribution and displacement magnitude. The design of the implant was made with CAD software, while the femoral bone used a topography scan. This study assigned two types of titanium alloy, Ti-6Al-4V, and Ti-13Nb-13Zr, to the design. SolidWorks was used to create and assemble designs into the femur, while the Abaqus workbench was employed to analyze stability and stress distribution. The displacement and stress distribution of the design is conducted based on walking conditions. Based on the simulation, the hollow-typed design with Ti-6Al-4V material developed the lowest displacement magnitude, 0.7751 µm. Meanwhile, the original design with Ti-13Nb-13Zr produced the lowest stress distribution, 177.11 Pa. In conclusion, removing additional features to the implant improves the implant stability but produces more stress than the implant that keeps its geometry integrity. The choice of materials is also the factor that affects the displacement and stress distribution.